Efektifitas Program Matrikulasi Bahasa untuk Meningkatkan Kemampuan Speaking Mahasiswa STAIBN Tegal - Pindha Kaptiningrum; Zaki Mubarok (SHAHIH: Journal of Islamicate Multidisciplinary, 2016)
Language Matriculation Program is a program of the Language Development Institution  of  STAIBN Tegal.  The purpose of the program is providing services to equip students to be able to speak English fluently. In this evaluative study, the researcher collected data relating to language matriculation program.  The data collection  is related to the learning process, the increasing of the students who participate  as well as the supporting and inhibiting factors in this program.  From the result of this evaluative study the author found that the language matriculation program that assist the students who have the desire and willingness to improve their English skills is good. However, the other goals should be added so that the program consist of the desire and the willingness of the students. Program Matrikulasi Bahasa adalah salah satu program dari Lembaga Pengembangan Bahasa STAIBN Tegal. Tujuan program ini adalah memberikan layanan bahasa inggris untuk membekali mahasiswa agar mampu berbahasa inggris secara lisan. Pada penelitian evaluatif ini, peneliti mengumpulkan data-data yang berkaitan dengan program matrikulasi bahasa. Pengumpulan data tersebut terkait dengan proses pembelajaran pada program ini, peningkatan mahasiswa yang mengikuti program ini serta faktor-faktor pendukung dan penghambat program ini. Dari hasil kajian evaluatif ini penulis menemukan bahwa program matrikulasi bahasa yaitu melayani mahasiswa yang memiliki keinginan dan kemauan untuk meningkatkan kemampuan bahasa inggris sudah bagus. Namun, perlu ditambahkan tujuan-tujuan lain agar program mencakup pada keinginan dan kemauan mahasiswa